On the use of BTDA-Bis-P polyamic acid as interphase in high performance thermoplastic composites - Nohara, Liliana Burakowski; Kawamoto, Aparecida Minhoko; Takahashi, Marta Ferreira Koyama; Nohara, Evandro Luís; Rezende, Mirabel Cerqueira (Revista Ciências Exatas, 2008)
The aim of present work is to present the synthesis of a PAA which will be used as interphase in the high performance thermoplastic composites manufacturing. For the composites manufacturing, the PAA is solubilized in a base and used in manufacture of suspension prepregging technique. The PAA studied was synthetized by using the BTDA dianhydride and Bis-P diamine reagents. In the present work, are presented the results by DSC (differential scanning calorimetry), TGA (thermogravimetric) and SEM (scanning electron microscopy) analyses that confirmed the synthesis. The DSC and TGA techniques indicated the glass transition (~248°C) and decomposition (~401°C) temperatures. These results show that the PAA/PI of type BTDA/Bis-P can be used as interphase in preparing of thermoplastic composites under broad window processing temperature.